Kyoto : (Kyoto City Tourist association, 1978)
Kyoto was the capital of Japan for about 1000 years from her establishment as Heian Kyo in 794 until the transfer of government to Kyoto in 1868 following the Imperial Restoration. Surrounded by magnificent hills, Kyoto with her poetry reflects the changing of the seasons, and has provided over the last twelve centuries a natural cradle for the art and culture of Japan, and a noble heritage for her people.